State-of-the-Art Review of Computational Static and Dynamic Behaviors of Small-Scaled Functionally Graded Multilayer Shallow Arch Structures from Design to Analysis - Hurdoganoglu, Dogus; Safaei, Babak; Sahmani, Saeid; Onyibo, Emmanuel Chukwueloka; Qin, Zhaoye (Springer, 2024)
Functionally graded multilayer shallow arch structures have gained significant attention due to their unique mechanical properties and potential applications. This review aims to provide a comprehensive overview of the static and dynamic behaviors of small-scaled functionally graded multilayer shallow arch structures, covering design and analysis aspects. The review begins by introducing functionally graded materials (FGMs) and their advantages in tailoring material properties. It then focuses on fabrication procedures for these structures. The design considerations are explored in detail, discussing various approaches for material composition grading and layer configuration. The influence of key parameters on structural behavior is examined, including material properties, layer thickness, and arch geometry. Mechanical analysis techniques for studying the static and dynamic behaviors of these structures are discussed. The review highlights the potential applications of FGMs in small-scaled shallow arch structures, such as bridges, tunnels, spaceships, and medical implants. This information is valuable for researchers interested in real-life applications. The review concludes by summarizing key findings and suggesting future research directions. It emphasizes investigating additional factors like temperature effects, geometric nonlinearities, and environmental conditions. The integration of advanced computational techniques with experimental validation is recommended for more accurate predictions and reliable design guidelines. Challenges in designing cost-effective and practical structures for real-world applications are acknowledged. Future research may focus on addressing these challenges and developing new techniques for large-scale engineering projects. The review provides insights into the fundamental scientific considerations and limitations of these structures. Overall, this state-of-the-art review serves as a valuable resource for researchers, engineers, and practitioners interested in designing and analyzing small-scaled functionally graded multilayer shallow arch structures. It offers insights into their computational static and dynamic behaviors and their potential applications in diverse fields.
Keywords: Free-Vibration Analysis; Geometrically Nonlinear-Analysis; Pasternak Elastic-Foundation; Inplane Stability Analysis; Mechanical-Properties; Curved Beams; Carbon Nanotubes; Cylindrical-Shells; Buckling Analysis; Large Deflection